2021
DOI: 10.1155/2021/6610603
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide, a TFEB‐Mediated Autophagy Agonist, Promotes the Viability of Random‐Pattern Skin Flaps

Abstract: Random skin flaps are commonly used in reconstruction surgery. However, distal necrosis of the skin flap remains a difficult problem in plastic surgery. Many studies have shown that activation of autophagy is an important means of maintaining cell homeostasis and can improve the survival rate of flaps. In the current study, we investigated whether liraglutide can promote the survival of random flaps by stimulating autophagy. Our results show that liraglutide can significantly improve flap viability, increase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Therefore, autophagy is a double-edged sword and may play different roles in different diseases and disease progress ( Wang et al, 2021 ). Our previous studies have also shown that the effect of autophagy on flap viability is controversial and needs further research ( Li et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021 ; Zhu et al, 2021 ; Lou et al, 2022 ). Therefore, the present study seeks to explore the effects of DATS and DATS-induced autophagy on the survival of perforator flaps and to reveal its possible regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, autophagy is a double-edged sword and may play different roles in different diseases and disease progress ( Wang et al, 2021 ). Our previous studies have also shown that the effect of autophagy on flap viability is controversial and needs further research ( Li et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021 ; Zhu et al, 2021 ; Lou et al, 2022 ). Therefore, the present study seeks to explore the effects of DATS and DATS-induced autophagy on the survival of perforator flaps and to reveal its possible regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, mediating autophagy is a method to promote the survival of random skin flaps, which has been supported by previous studies. 17,18 As a classical oxygen radicals scavenger, EDA has also been confirmed to possess the capability to mediate autophagy. Hence, we performed studies in vivo and vitro to investigate the role of EDA in promoting the survival of random skin flaps and its autophagy-related mechanisms (Figure 14).…”
Section: Discussionmentioning
confidence: 99%
“…43 Subsequently, Cleaved-Caspase3 is released from the damaged mitochondria and acted as an apoptotic executor in apoptosis. 18 Bcl-2 is a type of anti-apoptosis protein and prevents apoptosis from such mechanisms as inhibiting the function of proapoptotic gene p53, controling transcription factors and regulating the permeabilization of MOM. 44 Taken together, we found that the administration of EDA alleviated apoptosis of random skin flaps and MUVECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acacetin was reported to activate TFEB independent of the mTOR signaling pathway [112]. Furthermore, AMPK activation by PNU-282987, liraglutide and metformin induces mTOR inhibition and enhances TFEB-mediated lysosomal biogenesis and autophagy [113][114][115][116].…”
Section: Therapeutic Potential Of Targeting Tfeb In Neurodegenerative...mentioning
confidence: 99%